Psychological and pedagogical views on literary speech of children’s literature - Adamopoulou, Penelope; Oikonomaki, Andriani (eBooki.com.pl, 2014)
This article approaches storytelling as an educational method and learning tool by trying to identify how it can be applied in education. The aim is to examine how the fairy tale, an integral part of the oral tradition interacts with the literary texts and helps the reading child to become aware of literature and a conscious lifelong reader. This is a study which analyses children’s responses to literary stories read aloud and how they develop as individuals in a literature based instruction.
Keywords: responses; emotional development; children’s literature; storytelling